The production of ornamental pineapple in pots under different drip-irrigation depths - Silva Santos, Márcio Davi; Vieira do Bomfim, Guilherme; Moreira de Azevedo, Benito; Portugal Pinto de Carvalho, Ana Cristina; Newdmar Vieira Fernandes, Carlos (Revista Ceres, 2025)
The objective of this work was to evaluate the effects of irrigation depth on the commercial production of ornamental pineapple in pots. The experiment was carried out in a greenhouse located in Fortaleza, in the state of Ceará, Brazil. The experimental design was completely randomised, with five treatments and four replications. The treatments were irrigation depths estimated at 50, 75, 100, 125, and 150% of the evapotranspiration of a crop of edible pineapple. The plants were grown in one litre pots, with supplementary irrigation every two days. The variables evaluated were: number of leaves; length and width of the ‘D’ leaf; diameter of the rosette; plant height; rate of flowering; length and diameter of the peduncle, syncarp and crown; crown to syncarp ratio; commercial productivity and water-use efficiency. An increase in irrigation depth produced a linear increase in the number of leaves, width of the ‘D’ leaf and rosette diameter, but had no effect on the other variables. Water-use efficiency decreased linearly with the increases in irrigation depth. Despite influencing leaf growth, each irrigation depth results in plants suitable for commercialisation in pots. The smallest irrigation depth gives the greatest economy and water-use efficiency.